Investigation of high temperature effect on CFRP cutting mechanism based on a temperature controlled orthogonal cutting experiment. (15th July 2021) - Hou, Guoyi; Luo, Bin; Zhang, Kaifu; Luo, Yingxin; Cheng, Hui; Cao, Sipeng; Li, Yuan
Abstract: CFRP has been gradually used in the load-carrying structure with thicker component and stricter damage tolerance in aviation industry. However, the heat accumulation always occurs at hole exit-ply during thick CFRP drilling, resulting in temperature even higher than the glass transition temperature ( Tg ) of matrix, affected by which severe damages will occur based on an unknown cutting mechanism. Therefore, to investigate the new mechanism, this paper proposed a temperature controlled orthogonal cutting experiment by heating the cutting area to specified high temperature ranges (below and above Tg ) before cutting. The results show that the resin matrix will be only softened by the high temperature below Tg and lose part of its strength, but the cutting mechanism is almost not changed. As for temperature above Tg, the resin matrix will be heated into molten state thereby losing the support function for machined fibers, which changes the cutting mechanism at 90° < θ  < 180° into low efficiency cutting mode controlled by compressing stress. The fibers that lose support will be over bent and broken by flank face, and severe thermal mechanical damages including loose face, matrix cracking and fiber pull out can be captured at θ ~  150° of hole wall near exit.